2007
DOI: 10.2320/matertrans.mra2006193
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Characterization on Multi-Layered Thin Film Systems during Hydrogenation

Abstract: Ellipsometric characterization on the basis of multi-layered modeling is proposed to describe the optical and electrical property transients of hydrogenated films. In particular, two-step modeling is developed to make ellipsometric characterization on the yttrium film and the palladium capped yttrium film deposited on the SiO 2 glass substrate. In the former, Y 2 O 3 film deposited on SiO 2 substrate is prepared to estimate the dielectric response of yttrium oxide layer as the first step. These data are furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Figure 2a is the three-layered optical model used for simulation, where layer-1 was treated as mixture of polycrystalline silicon and amorphous silicon, layer-2 was pure polycrystalline silicon and the glass substrate was treated as Cauchy glass with backside reflection [15,16]. The fitting of layer-1 used Bruggman's Effective Medium Approximation (EMA) model [17], where Tauc-Lorentz and Gaussian oscillators were used for poly-Si and Cody-Lorentz [18] and Gaussian oscillators for a-Si [19]. The fitting had very small mean squared error (MSE)~2.5 to the experimental values of psi and delta.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2a is the three-layered optical model used for simulation, where layer-1 was treated as mixture of polycrystalline silicon and amorphous silicon, layer-2 was pure polycrystalline silicon and the glass substrate was treated as Cauchy glass with backside reflection [15,16]. The fitting of layer-1 used Bruggman's Effective Medium Approximation (EMA) model [17], where Tauc-Lorentz and Gaussian oscillators were used for poly-Si and Cody-Lorentz [18] and Gaussian oscillators for a-Si [19]. The fitting had very small mean squared error (MSE)~2.5 to the experimental values of psi and delta.…”
Section: Methodsmentioning
confidence: 99%
“…Though there are numerous works on Y hydrogenation, 8,13-16 only a few of them used ellipsometry to monitor the process. 8,16 To our knowledge, none of the published data include the dynamics of the phase transition, but instead focus on the beginning and end points of hydrogenation. For a sensor application, however, it is important to understand the structural changes in the Y film during the hydrogenation process and their impact on the ellipsometry signal.…”
Section: Introductionmentioning
confidence: 99%
“…YH 3 is formed once the temperature of YH 2 is lowered to 200°C at a similar hydrogen pressure [2]. Further research showed that Y, in the form of a thin film (usually capped), does not powderize during hydrogenation, in contrast to bulk Y samples, allowing its electrical and optical properties to be extensively studied [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%